GAMBARAN INDEKS MASSA TUBUH PENDERITA TUBERKULOSIS (TB) POSITIF YANG MELAKUKAN PENGOBATAN DI GERDUNAS TB PARU RUMAH SAKIT UNDATA PALU SULAWESI TENGAH - Fadhalna Fadhalna; Ihwan Ihwan; I Nengah Suwastika (Biology Department, Mathematics and natural science, Tadulako University, 2017)
Research on the description of the patient's BMI (body mass index) of tuberculosis (TB) in the positive treatment of pulmonary tuberculosis at the unit of integrated movement prevention of tuberculosis Undata Hospital Palu has been implemented since April until September 2015. This research aimed to look at the dynamics of BMI of patients during treatment. The method used was the retrospective design patients who present within 2014, which qualified as research sample. There are 45 respondents of eligible subjects complete data up to the end of treatment. The results showed a changeof each category of BMI from the early phase to the final phase of treatment. In theearly phase of treatment, is very thin and thin BMI were 30 respondents fromcategory 1 and category 2, its hows that most patients with early diagnosis of tuberculosis have a BMI below normal. While in the early phase until the end of treatment showed a significant frequency changes in norma lBMI reaches 24.5% categorized 1 and 0.1% incategory 2. This is due to irregular treatment undergone by the patient from the early phase to the final phase of treatment. This indicates that the category 1 more treatment success which is marked by the increasing quality of BMI’s Patients return to normal. While in Category 2 does not show the amount of success, because with drawing treatment.